Determinan Penanaman Modal Asing Di Pulau Jawa - Rizky Handayani; Ismadiyanti Purwaning Astuti (FEB Universitas Sultan Ageng Tirtayasa, 2022)
Development is the most important thing in the progress and prosperity of a region. The implementation of development on the island of Java requires substantial funds but the funds available domestically are not sufficient. This condition prompted the government to look for alternative sources of financing from abroad by foreign investment. This study aims to analyze the effect of government spending, inflation, and the minimum wage on foreign investment in Java. The data analysis used is panel data analysis method. The results of the study indicate that the government expenditure variable has a positive and significant effect on foreign investment in Java, the inflation variable has a positive and insignificant effect on foreign investment in Java, and the minimum wage variable has a negative and significant effect on foreign investment in Java.